Analisa Perubahan Tata Guna Lahan Terhadap Resapan Air di Desa Kemilau Baru Kabupaten Ogan Komering Ulu - Lucyana Lucyana; Azwar Azwar (Jurnal Deformasi, 2022)
ABSTRACTKemilau Baru area, one of the villages located in East Baturaja District, Ogan Komering Ulu Regency, this village is a new village from the division of the Tanjung Baru Village area. formerly a forest area and untouched, but now with the increasing number of residents, this area has undergone many changes in the form of all fields, such as now there are many residential areas, sports places, places of worship and so on. And for the catchment area that has changed a lot. The purpose of this study was to determine the effect of land use changes on water absorption in the area of Kemilau Baru Village, District. East Baturaja, Regency. Ogan Komering Ulu. This research procedure includes the stages that can be presented in a flow chart. Data collection methods in this study are primary data and secondary data. Based on research conducted by researchers, the results obtained that Kemilau Baru Village has an area of 2,438.05 ha, has areas such as settlements with an area of 680 ha and vacant land with an area of 908.05 ha, agriculture with an area of 800 ha, offices with an area of 100 ha and trade and services with an area of 20 ha. Residential land use 28%, vacant land 33% agriculture 32%, offices 5% and trade and services 2%.From the results of the analysis obtained the value of runoff discharge: 36% of the rain that fell in Kemilau Baru Village became surface runoff. This shows that Kemilau Baru Village has a moderate runoff coefficient.